2014
DOI: 10.1039/c4nr05371k
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Cu2S and CuS nanorod and nanowall arrays: preparation, properties and application in CO2 photoreduction

Abstract: Copper sulfide semiconductors made from earth-abundant elements have an optical absorption edge at ca. 1.2 eV, nearly ideal for solar energy harvesting. We report the growth and formation mechanism of vertically oriented arrays of copper sulfide nanostructures formed by electrochemical anodization. Key parameters that affect the morphology and phase of the nanostructures are type and strength of electrolyte, anodization voltage and duration. Cu₂S and CuS nanostructures were obtained on both copper foil and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(73 citation statements)
references
References 78 publications
9
64
0
Order By: Relevance
“…In addition, the peak positions of Cu 2p for Cd-1-T4 are apparently shifted to much lower binding energy region, compared with those of Cd-0-T6 and Cd-1-T6, illustrating the formation of much more Cu + on the surface. These results are in well agreement with the observation of S 2p region and previous reports 30, 52 . The reason for the formation of Cu 2 S may be ascribed to the amount of thiourea and chloride ions from the addition of cadmium chloride in the precursor solution 45, 5254 .
Figure 7XPS analysis of as-synthesized samples in the Cu 2p, Cd 3d and S 2p regions.
…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…In addition, the peak positions of Cu 2p for Cd-1-T4 are apparently shifted to much lower binding energy region, compared with those of Cd-0-T6 and Cd-1-T6, illustrating the formation of much more Cu + on the surface. These results are in well agreement with the observation of S 2p region and previous reports 30, 52 . The reason for the formation of Cu 2 S may be ascribed to the amount of thiourea and chloride ions from the addition of cadmium chloride in the precursor solution 45, 5254 .
Figure 7XPS analysis of as-synthesized samples in the Cu 2p, Cd 3d and S 2p regions.
…”
Section: Resultssupporting
confidence: 94%
“…These results are in well agreement with the observation of S 2p region and previous reports 30, 52 . The reason for the formation of Cu 2 S may be ascribed to the amount of thiourea and chloride ions from the addition of cadmium chloride in the precursor solution 45, 5254 .
Figure 7XPS analysis of as-synthesized samples in the Cu 2p, Cd 3d and S 2p regions. ( a ) Samples prepared by changing the amount of Cd content with fixing thiourea, and ( b ) Samples obtained by modulating the contents of both Cd and thiourea.
…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…For the peaks of 161.3 (S 2p 3/2 ) and 163.2 eV (S 2p 1/2 ) are characteristic of sulfide, which should be attributed to the S−S bond in graphene‐like multilayered structure of CuS . The peaks at 162.2 (S 2p 3/2 ) and 163.2 eV (S 2p 1/2 ) are indicative of CuS, and the peak of 168.5 eV can be ascribed to the sulfate species (e. g. CuSO 4 ) formed by the oxidation of CuS in air . These results indicated that the as‐prepared products are mainly composed of Cu 2+ and S 2− .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with vacuum deposition processes-electrochemical anodization processes are scalable, the process instrumentation cost is low, and it is relatively simple to adjust anodization conditions in order to allow tuning of nanoscale morphology as well as the semiconducting and optical properties of the resulting semiconductors. Therefore, anodically formed copper-based nanostructures are attracting increased attention [2][3][4]. The use of copper oxide nanostructures is motivated by the Earth abundance and relatively low price of copper, coupled with the high performance potential of copper oxide for several leading edge applications; these include semiconductor catalysis, solar photovoltaics and biosensing [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%